Hybrid Metal-Dielectric Photonic Crystals with Enhanced Plasmonic-Photonic Interaction - Bahrami, M. Reza; Lobaz, Volodymyr; Peukert, Wolfgang; Korovin, Alexander V.; Peschel, Ulf; Romanov, Sergei G. (13th International Conference on Transparent Optical Networks (ICTON), 2011)
Control on the optical response of 2-dimensional colloidal photonic crystals was achieved by combining them with thin metal films. In such hybrids the light transport depends on the parameters of the sphere lattice and the topology of the metal film. This approach allows mixing Bloch modes and surface plasmon polariton modes in the total optical response of hybrid architectures. Stronger modification of the hybrid's optical properties was achieved in the case of tighter light confinement.
Keywords: hybrid photonic crystal; surface plasmon polariton; optical transmission